2007
DOI: 10.1002/app.25862
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new aromatic polyesters containing biphenyl side groups

Abstract: Aromatic polyesters containing biphenyl side groups were synthesized by phase-transfer catalyzed interfacial polycondensation of 1-(4-biphenylyl)-1,1-bis(4-hydroxyphenyl) ethane (BBHPE) with terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), and a mixture of TPC/IPC (50 : 50 mol ratio). Copolyesters were synthesized by utilizing different molar proportions of BBHPE and 4,4 0 -isopropylidenediphenol (BPA) with IPC and TPC. The inherent viscosities of polyesters were in the range 0.44-1.26 dL/g. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Dimethyl substitutions on bisphenols results into an asymmetric segment, which could have resulted in less efficient packing than unsubstituted bisphenols. The T g values of polyesters obtained in the present study were comparable with T g values (232–256°C) of corresponding polyesters containing biphenyl pendent groups 5…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Dimethyl substitutions on bisphenols results into an asymmetric segment, which could have resulted in less efficient packing than unsubstituted bisphenols. The T g values of polyesters obtained in the present study were comparable with T g values (232–256°C) of corresponding polyesters containing biphenyl pendent groups 5…”
Section: Resultssupporting
confidence: 86%
“…It was observed that the T g values for NABP‐IPC and NABP‐TPC were higher than those of the corresponding polyesters based on BPA. The T g values for polyesters based on BPA‐IPC and BPA‐TPC are 181°C and 210°C, respectively 5. It was observed that the T g values for NABP‐based polyesters with IPC, TPC and IPC/TPC were higher than those of the corresponding polyesters based on o ‐NABP.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…For this purpose, what is known as Taguchi's method was used [27–29]. The main advantage of this methodology is the possibility to handle with a larger numbers of control parameters with relatively small amount of trials [30–32].…”
Section: Introductionmentioning
confidence: 99%